Assessing Admission Criteria for Early and Mid-Career Students: Evidence from a U.S. MPA Program - Darolia, Rajeev; Potochnick, Stephanie; Menifield, Charles E. (Education Policy Analysis Archives, 2014)
As applications for graduate and professional degree programs have reached unprecedented levels over the past decade, the applicant pool has become more diverse with more mid-career students deciding to return to school. Given the growth and diversification of the graduate applicant pool, many graduate programs are struggling to develop stronger admission package criteria that assure students admitted to their program have the pre-requisite skills needed to succeed. We examine which commonly used graduate admission criteria, particularly the Graduate Record Exam (GRE), correlate with the academic performance of both early and mid-career professional students. Using data from student files from a southeastern U.S. graduate public administration program, we find that the GRE score, undergraduate grade point average, and type of undergraduate institution are good predictors of graduate performance, but that the value of these admission criteria differs for early and mid- career students.